Stability of surgical rib fixation hardware after repeat chest trauma - Jackson Rucker Staggers (Journal of Emergencies, Trauma and Shock, 2020)
Surgical management of rib fractures has long been a controversial topic, but improvements in rib plating technology have led to a recent increase in interest among surgeons. Unfortunately, follow-up data are limited in patients following rib fracture plating. We present a unique case of an adult male who had multiple ribs plated for symptomatic rib fracture nonunions and developed periprosthetic fractures following repeat trauma several months later. A 57-year-old male with a history of trauma was treated for symptomatic nonunion of several left lateral ribs with surgical rib fixation. He tolerated the procedure well and had significant improvement in his symptoms on follow-up. Several months later, he was hit by a motor vehicle while riding his bicycle. He was found to have flail chest with lateral segmental rib fractures of the first through second ribs, posterior periprosthetic fractures of the seventh through tenth ribs, and lateral fractures of the eleventh and twelfth ribs. The rib plating hardware was completely intact, except for a single displaced seventh rib screw. To our knowledge, this is the first case report of repeat chest trauma following rib plating. Interestingly, the patient developed posterior periprosthetic fractures, and hardware was completely intact except for a single screw that was displaced. The goal of this report is to describe the unique fracture pattern of a flail chest with prior rib plating and to describe potential revision plating techniques and complications that surgeons may encounter in the management of trauma patients with prior rib plating.